ISLAMIC LAW ANALYSIS OF THE ROLE OF THE HEFORSHE CAMPAIGN IN PROTECTING WOMEN IN THE PALEMBANG COMMUNITY - Riska, Mira Novita; Nurnazli, Nurnazli; Zuhraini, Zuhraini (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2024)
The title of the article is HeForShe's Role in Palembang Society. She invites men of all ages as equal partners in building a women's rights movement and implementing a shared vision of gender equality that benefits all humanity. The campaign sought to actively involve men and boys in a movement initially conceived as "women's struggle by women. The first issue raised was the role of HeForShe's campaign in protecting women in Palembang society. Second is a review of Islamic law on HeForShe's role in protecting women. This type of research is research this termasuk todalam descriptive research qualitative meetup will research yan g digunwill examine the condition of scientific objects, dimana researcher As a key instrument, data collection techniques are carried out in combination, inductive data analysis and qualitative research results emphasize meaning rather than generalization. From the results of this study, it can be concluded that the achievement of gender equality through the HeForShe Campaign is realized through the role of HeForShe in Indonesia to support and achieve gender equality in the form of training, socialization, and education aimed at the community, workers, and students. One of the activities is raising awareness among men and women about the Sriwijaya Smart Women's Movement (GPCS). Women's protection is included in the Adz-Dzaruriyah maslahat, which is an effort to protect women; women need this protection to carry out their rights and obligations properly. The policy of maslahah must be in accordance with the objectives of Islamic Law; that is, it must not contradict the Qur'an and the Sunnah and must be in accordance with the purpose of Islamic Law, namely al-maqāṣid al-Syari’ah, according to researchers, to be appropriate and appropriate.